Faktor – Faktor Keputusan Pembelian Barang Tiruan Tinjauan Perspektif Islam : Studi Kasus Mahasiswa UINSU - Najwa Felisha Lubis; Reni Ria Armayani Hasibuan; Nurbaiti Nurbaiti (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the influence of price factors, social factors, psychological factors, and knowledge factors on the decision to purchase counterfeit goods among students of the State Islamic University of North Sumatra (UINSU) from an Islamic perspective. This research uses a mixed methods approach with a sequential exploratory design, starting with in-depth interviews with students who have purchased or used counterfeit goods, followed by the distribution of questionnaires to 100 respondents selected using purposive sampling technique. Qualitative data were analyzed thru data reduction, data presentation, and conclusion drawing, while quantitative data were analyzed using multiple linear regression with the help of SPSS after passing validity, reliability, and classical assumption tests. The research results show that the decision to purchase imitation goods is influenced by price, social, psychological, and knowledge factors, with price being the most dominant factor and the consideration of Islamic values in the decision-making process. The price factor and the knowledge factor have a partially positive and significant impact on purchasing decisions, while the social factor and psychological elements do not have a significant influence. The four independent variables significantly influence purchasing decisions (Sig. = 0.000) and explain 65.4% of the variance in purchasing decisions (Adjusted R square = 0.654). These findings indicate that consumer purchasing decisions are more rational, particularly in terms of price affordability and product knowledge, while still considering the values of honesty, benefit, and avoiding elements of deception, uncertainty, and extravagance from an Islamic perspective.